A13 WHOLE EXOME SEQUENCING OF OVER 1000 PEDIATRIC IBD PATIENTS FROM A SINGLE CENTRE IDENTIFIES MONOGENIC FORMS OF IBD. (1st March 2018) - Crowley, E; Warner, N; Fiedler, K; Murchie, R; Church, P; Walters, T D; Griffiths, A; Muise, A
Abstract: Background: Inflammatory bowel disease (IBD) has a multifactorial aetiology, with complex interactions between genetic and environmental factors. Recent studies suggest an increasing spectrum of monogenic disease in the very young. The prevalence of these mutations in older children is unknown. Aims: To determine the incidence of monogenic forms of IBD in a typical cohort of pediatric IBD patients and identify any phenotypic characteristics suggestive of a monogenic cause. Methods: 2, 431 unique participants underwent whole exome sequencing (WES), including 1, 098 IBD probands. This data was interrogated for a panel of 51 genes known to be associated with monogenic IBD. The Genome Analysis Toolkit (GATK) was used to identify highly penetrant rare variants of interest. Sanger sequencing verified variant genotypes. A clinical database was reviewed to ascertain phenotypic characteristics. Results: A single centre retrospective study identified 1, 098 index cases, diagnosed over a 12 year period (2003–2015) who underwent WES. 2431 unique participants (302 trios, 31 quads, 29 affected siblings). Of sequenced affected cases, 60% CD, 40% UC/IBD-U. 16% < 6.9 years, 22% 7–10.9 years, 62% > 11 years. Across the 51 genes, 19 protein coding variants predicted to be deleterious were identified in 54 patients, which were high quality and rare (maf <0.01). XIAP, DOCK8 and CYBB were the most commonly identified gene variants within the cohort. Overall, approximately 4.9% of patients in a typical cohort of Pediatric IBD patients were found to have monogenic disease. Conclusions: WES of this largest pediatric cohort to date confirms the highly varied phenotypic spectrum of IBD associated with monogenic disease. Whilst many children with causal VEOIBD mutations were diagnosed < 1 year of age, a significant number of older children were identified. Characterising genotypic-phenotypic features may provoke earlier recognition which will allow novel therapeutic approaches in this paediatric IBD population. Funding Agencies: None